Late Engine Activity in Neutron Star Mergers and Its Cocoon: An Alternative Scenario for the Blue Kilonova - Hamid Hamidani; Shigeo S. Kimura; Masaomi Tanaka; Kunihito Ioka (The Astrophysical Journal, 2024)
Follow-up observations of short gamma-ray bursts (sGRBs) have continuously unveiled late extended/plateau emissions, attributed to jet launch due to late engine activity, the nature of which remains enigmatic. Observations of GW170817 have confirmed that sGRBs are linked to neutron star (NS) mergers, and discovered a kilonova (KN) transient. Nevertheless, the origin of the early blue KN in GW170817 remains unclear. Here, we investigate the propagation of late jets in the merger ejecta. By analytically modeling jet dynamics, we determine the properties of the jet-heated cocoon, and estimate its cooling emission. Our results reveal that late jets generate significantly brighter cocoons compared to prompt jets, primarily due to reduced energy loss by adiabatic cooling. Notably, with typical late jets, emission from the cocoon trapped inside the ejecta can reproduce the blue KN emission. We estimate that the forthcoming Einstein Probe mission will detect the early cocoon emission at a rate of $\sim {2.1}_{-1.6}^{+3.2}$ yr ^−1 , and that optical/UV follow-ups in the LIGO-Virgo-KAGRA O5 run will be able to detect $\sim {1.0}_{-0.7}^{+1.5}$ cocoon emission events. As an electromagnetic counterpart, this emission provides an independent tool to probe NS mergers in the Universe, complementing insights from sGRBs and gravitational waves.